A Methodology to Integrate Security and Cost-Effectiveness in ATM. (31st January 2014) - Matarese, Francesca; Montefusco, Patrizia; Neves, José; Rocha, André
The objective of this paper is the definition of a new methodology for carrying out security risk assessment in the air traffic management (ATM) domain so as to enhance security awareness and integrate secure and cost-effective design objectives. This process is carried out by modelling the system, identifying the assets, threats and vulnerabilities, prioritizing the threats and proposing cost-effective countermeasures for the weaknesses found. ATM security is concerned with securing ATM assets in order to prevent threats and limit their effects on the overall aviation network. This effect limitation can be achieved by removing the vulnerability from the system and/or increasing the tolerance in case of component failures due to attacks. The security risk assessment methodology proposed is based on what is currently being done by the industry (the International Civil Aviation Organization (ICAO) and the International Standard Organization (ISO), etc.).